Navigating Ocean Literacy in Europe: 10 years of history and future perspectives - MOKOS, MELITA; DE-BASTOS, ELIANE; REALDON, GIULIA; WOJCIESZEK, DOMINIKA; PAPATHANASIOU, MARTHA; TUDDENHAM, PETER (Mediterranean Marine Science, 2022)
Ocean Literacy (OL) emerged in the USA in the 2000s as a concept developed for the education system aimed at teachers. In 2011, it gained the attention of European educators who formed the first OL network in Europe, the European Marine Science Educators Association (EMSEA). Parallel to that initiative, Portugal started the first initiative to adopt OL content into formal education. Since then, there has been a major shift towards a more literate society in Europe. This paper reviews the development of OL in Europe elaborates the role of OL for the sustainable future of the European seas, and provides recommendations for OL actions.